Coherence for nutrition: insights from nutrition-relevant policies and programmes in Burkina Faso and Nigeria. Issue 10 (21st September 2021) - Billings, Lucy; Pradeilles, Rebecca; Gillespie, Stuart; Vanderkooy, Anna; Diatta, Dieynab; Toure, Mariama; Diatta, Ampa Dogui; Verstraeten, Roos
Abstract: There is consensus that policy coherence is necessary for implementing effective and sustainable approaches to tackle malnutrition. We look at whether policies and programmes provide a coherent pathway to address nutrition priorities and if programmes are designed to deliver interventions aligned to the nutrition policy agenda in Nigeria and Burkina Faso. A systematic desk review was performed on nutrition-relevant policy and programme documents, obtained through grey literature searches and expert recommendations. We developed a framework with an impact pathway structure that includes five process steps, which was used to guide coding, data reduction and synthesis and structure the analysis. We assessed internal coherence along process steps within a given document and external coherence across process steps for explicitly linked policy/programme pairs. The majority of policies and programmes had partial internal coherence for both countries. The identification of relevant nutrition interventions to address challenges and reach objectives was the strongest connection within policies (16 out of 45 had complete coherence), while among programmes, the strongest connection was coverage indicators that measure interventions (9 out of 21 had complete coherence). Eight programmes explicitly referenced at least one nutrition-relevant policy, with a total of 16 linked policy/programme pairs (13 pairs for Burkina Faso and 3 for Nigeria) across health, nutrition, agriculture and social focus areas. However, none of the linked pairs were assessed to have complete external coherence, suggesting that priorities at the policy level are not fully realized nor translated at the programme level. This study offers a new approach for the assessment of policy and programme coherence and specifically examines policy and programme linkages. We conclude that improved leadership on country priority setting and better alignment for nutrition within and across sectors is needed to enhance the effectiveness of nutrition investments.